(untitled) (The Agriculturists, 2015)
An experiment was conducted at Char Martin under Multi Location Testing site in Laxmipur district during Rabi season of 2011-12 & 2012-13 with different fertilizer doses to find out the economic fertilizer dose for soybean variety BARI Soybean 6 under farmers field condition. Four fertilizer combinations viz; T1 : 17-27-55-2.7-2.0-0 kg ha-1 of N-P-K-S-Zn-B (Soil Test Based fertilizer), T2 : 25- 25-50-10-0-0 kg ha-1 of N-P-K-S-Zn-B (Fertilizer Recommendation Guide, 2005 based fertilizer), T3 : 28-13-0-0-0-0 kg ha-1 of N-P-K-S-Zn-B (Farmers practice) and T4: Native fertility (control) were selected. All the yield and yield contributing characters of BARI Soybean 6 varied significantly with the different fertilizer treatments. The highest seed yield (2.99 t ha-1) was recorded from plants treated with T1 which was statistically similar to T2. The lowest seed yield (1.74 t ha-1) was obtained from T4. The highest gross return (Tk.104650 ha-1), net return (Tk. 56375 ha-1) and benefit cost ratio (2.16) were obtained from T1 and the lowest gross return (Tk. 60900 ha-1), net return (Tk.19900 ha-1) and BCR (1.48) was obtained from T4 . The Agriculturists 2014; 12(2) 98-102